Biomimetic Polycaprolactone‐Graphene Oxide Composites for 3D Printing Bone Scaffolds - Iman Sahafnejad‐Mohammadi; Sadegh Rahmati; Najmeh Najmoddin; Mahdi Bodaghi (Macromolecular Materials and Engineering, 2023)
Abstract Bone shows a radial gradient architecture with the exterior densified cortical bone and the interior porous cancellous bone. However, previous studies presented uniform designs for bone scaffolds that do not mimic natural bone's gradient structure. Hence, mimicking native bone structures is still challenging in bone tissue engineering. In this study, a novel biomimetic bone scaffold with Haversian channels is designed, which approximates mimicking the native bone structure. Also, the influence of adding graphene oxide (GO) to polycaprolactone (PCL)‐based scaffolds are investigated by preparing PCL/GO composite ink containing 0.25% and 0.75% GO and then 3D printing scaffolds by an extrusion‐based machine. Scanning electron microscopy (SEM) is used for morphological analysis. SEM reveals good printability and interconnected pore structure. The contact angle test shows that wettability reinforces with the increase of GO content. The mechanical behavior of the scaffolds under compression is examined numerically and experimentally. The results indicate that incorporation of GO can affect bone scaffolds' Young's modulus and von Mises stress distribution. Moreover, the biodegradation rates accelerate in the PCL/GO scaffolds. Biological characterizations, such as cell growth, viability, and attachment, are performed utilizing osteoblast cells. Compared to pure PCL, an enhancement is observed in cell viability in the PCL/GO scaffolds.